Brachial Plexus Injuries in Adults: A Narrative Review of the Literature - Ananias, Joaquín; Pino, Paula A. (Revista Chilena de Ortopedia y Traumatología, 2022)
Traumatic brachial plexus injuries comprise a wide spectrum of lesions that are potentially devastating to the functionality of the patients. The aim of the present review is to perform a narrative review of the literature focused on the diagnosis and study of brachial plexus injuries in adults, in addition to providing basic guidelines on the management of this complex pathology.Level of evidence: Level V.
Keywords: upper limbs; nerve grafts; microsurgery; brachial plexus; nerve transfers